Concomitant bacteria in the blood of malaria patients in Owerri, southeastern Nigeria - Ukaga, CN; Orji, CN; Orogwu, S; Nwoke, BEB; Anosike, JC; Udujih, OS; Onyeka, PIK; Awujo, NC (Tanzania Journal of Health Research, 2009)
No Abstract.